Pengaruh Struktur Aktiva, Debt to Assets Ratio, Return on Equity Ratio dan Dividend Payout Ratio Terhadap Price Book Value: Studi Empiris pada Perusahaan Non-Perbankan yang Tergabung dalam Indeks LQ45 di Bursa Efek Indonesia Periode 2019-2023 - Juli Ani; Slamet Mudjijah (Journal of Management and Social Sciences, 2024)
This research examines the impact of Asset Structure, Debt to Assets Ratio, Return on Equity, and Dividend Payout Ratio on Price to Book Value. It focuses on non-banking firms listed in the LQ45 Index on the Indonesia Stock Exchange from 2019 to 2023. Utilizing secondary data and purposive sampling, the study analyzed a sample of 16 non-banking companies out of a population of 38. Multiple linear regression analysis was conducted using SPSS version 22. The results show that Debt to Assets Ratio, Return on Equity, and Dividend Payout Ratio affect Price to Book Value, while Asset Structure does not. Asset Structure does not..